Influence of ship dynamics modelling on the prediction of fishing vessels roll response in beam and longitudinal waves. (15th January 2018) - Míguez González, Marcos; Bulian, Gabriele
Abstract: Fishing is one of the most risky occupations worldwide. Many accidents are due to stability failures, and dynamic stability phenomena in waves are among the possible causes. Due to time, cost and regulatory lacks, these phenomena are not addressed during design of fishing vessels. High fidelity six degrees of freedom (6-DOF) codes can cope with these phenomena, but their complexity, cost and time of application, limit their use to high-end vessels. The use of less demanding approaches appears more suited for the fishing sector. The scope of this paper is to compare a 6-DOF blended code, 1-DOF nonlinear roll models and simplified analytical formulae, in order to assess the level of dispersion of the obtained roll motion predictions among tools with different levels of complexity. The roll response for a medium-sized stern trawler is investigated in regular beam and longitudinal waves, at zero speed. Results from the simplified models are in fair agreement with those from the 6-DOF code, at least for moderate wave steepnesses. Simplified models could provide a valuable tool for the assessment of fishing vessels behaviour at the early design stage, considering also their ease of implementation within typical existing naval architecture software. Highlights: Fishing vessels are the focus of the study. Roll motion in regular waves is simulated for a mid-sized trawler. Beam waves (harmonic resonance) and longitudinal waves (parametric roll) are considered. Mathematical models with different levels of complexity are compared. Results are discussed in view of implementation in the design process.